AIDS related systemic non-Hodgkin's lymphoma. Issue 5 (1st October 2000) - Powles, Tom; Matthews, Gail; Bower, Mark
Abstract : Objective: To review the current literature on HIV associated non-Hodgkin's lymphoma. Methods: A comprehensive Medline/Pubmed search of articles pertaining to HIV associated non-Hodgkin's lymphoma as well as personal experience from the treatment of over 200 patients at the Chelsea and Westminster Hospital, one of the largest centres for the management of HIV disease in Europe. Conclusion: High grade B cell non-Hodgkin's lymphoma is the second commonest tumour affecting people with HIV. The incidence of this tumour is not declining following the introduction of highly active antiretroviral therapy. Chemotherapy has been employed with modest success in this group of patients; however, the prognosis remains worse than for immunocompetent patients. Advances in molecular genetics and virology have led to a greater understanding of the biology of these tumours. However, these advances have yet to be translated into improvements in the clinical management of patients with AIDS associated non-Hodgkin's lymphoma.